ASSOCIATION BETWEEN KNOWLEDGE OF HELMINTHIASIS AND DEWORMING BEHAVIOR AMONG COMMUNITY MEMBERS IN GASING, BANYUASIN REGENCY, INDONESIA - Kusumasari, Peni; Widyastuti; Pratiwi, Rini (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Helminth infections remain a significant public health problem, particularly in areas with limited sanitation. The success of deworming programs is strongly influenced by community behavior, which is partly determined by the level of knowledge. This study aimed to analyze the relationship between knowledge of helminth infections and deworming medication-taking behavior among residents of Gasing Village, Banyuasin. This study employed an analytic observational design with a cross-sectional approach involving 44 respondents selected through convenience sampling. Data were collected through interviews using a structured questionnaire. The results were analyzed using univariate and bivariate analyses, with the Chi-square test applied to assess the association between variables. The findings showed that 40,9% of respondents had a good level of knowledge regarding helminth infections, and 68,2% demonstrated good deworming medication-taking behavior. Bivariate analysis revealed a significant relationship between knowledge of helminth infections and deworming medication-taking behavior (p=0.001). Strengthening community health education is necessary to improve adherence to deworming medication, thereby supporting helminth infection control programs.